'Building Schools for the Future': 'transformation' for social justice or expensive blunder?. (2nd September 2012) - Mahony, Pat; Hextall, Ian
<x xml:space="preserve">Abstract</x> This article is based on research undertaken between 2009 and 2012 into the former Labour government's extremely ambitious 'Building Schools for the Future' (BSF) Programme and its withdrawal by the Coalition government. The project, which utilises analysis of policy documents, case studies in six local authorities (LA) and semi‐structured interviews with national and local policy actors, is being funded by Roehampton's Centre for Educational Research in Equalities, Policy and Pedagogy and the British Academy (SG100363). The focus of this article is the implications for social justice of BSF and its subsequent withdrawal. The structure of the article comprises an introduction to BSF and a summary of some of the main issues arising from it. We then move on to explore the social justice dimension of BSF as it is expressed in LA documents and in relation to the social policy aspirations of the former Labour government. In July 2010 the Coalition government discontinued the BSF programme and we track events and policy from that time, particularly focussing on the radical shift away from Labour's transformational and communitarian agenda in favour of criteria based on efficiency and value‐for‐money. We present data from our interviews with local actors on the equality and social justice impacts of this re‐orientation of policy. We conclude by arguing against the view that Labour abandoned social justice suggesting that BSF was one of a number of policies through which equality was pursued, albeit by stealth.